Mathematics Preservice Teachers’ Views on Mathematical Literacy - Ani Afifah; Miftahul Khoiri; Nur Qomaria (International Journal of Trends in Mathematics Education Research, 2018)
This study aims to know mathematics preservice teachers’ common sense understanding of mathematical literacy. The results will later be used to design a learning program to introduce mathematical literacy to preservice teachers so that they have a better understanding of mathematical literacy. Data were collected by giving questionnaires to one hundred and eight mathematics preservice teachers. The result showed that mathematics preservice teachers’ views on mathematical literacy can be categorised into 5 areas: 1) ability that has to do with problems in people’s daily life, 2) communicating using mathematics concepts and properties, 3) interpreting mathematical sentences into everyday language or vice versa, 4) activity related to reading and writing about mathematics, 5)  basic knowledge of mathematics. Preservice teachers agreed that learning mathematics in schools should connect mathematical concepts with real-life problems. They are also ready to increase the mathematical literacy abilities of their future students.